Fast Hierarchy Preserving Graph Embedding via Subspace Constraints - Du, Lun; Chen, Xu; Chen, Mengyuan; Wang, Yun; Long, Qingqing; Xie, Kunqing (Proceedings of IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2021)
Hierarchy preserving network embedding is a method that project nodes into feature space by preserving the hierarchy property of networks. Recently, researches on network representation have considerably profited from taking hierarchy into consideration. Among these works, SpaceNE 1 [1] stands out by preserving hierarchy with the help of subspace constraints on the hierarchy subspace system. However, like all other hierarchy preserving network embedding methods, SpaceNE is time-consuming and cannot generalize to new nodes. In this paper, we propose an inductive method, FastHGE, to learn node representations more efficiently and generalize to new nodes more easily. Empirically, the experiment of node classification demonstrates that the convergence speed of FastHGE is increased by 30 times in the case of the same accuracy with SpaceNE.